Analisis Faktor-Faktor yang Mempengaruhi Kinerja Inspektur Penerbangan Kantor Otoritas Bandar Udara Indonesia - Hasanuddin (Politeknik Penerbangan Makassar, 2021)
The objectives of this study are: (1) to study and analyze work skills, motivation and communication which significantly and significantly affect the performance of the Flight Inspector at the Makassar Region V Airport Authority and (2) to assess and analyze the dominant and significant factors that affect the inspector's performance. Flight Authority Office Makassar Region V Airport. This research was conducted at the operation of the Flight Inspector at the Makassar Region V Airport Authority Office with a population of 51 Flight Inspectors at the Makassar Region V Airport Authority Office. The research sample used purposive sampling method (30%), namely 47 respondents. The data analysis used was descriptive to explain the characteristics of the respondent and the research descriptive, while to analyze the quantitative data using multiple regression analysis tools. This study examines the factors that affect the operational performance of the Flight Inspector at the Makassar Region V Airport Authority. The results showed that the average value of R, R2 and R2 had a significant effect. The regression coefficient (B) for the competency variable (X1), motivation (X2) and constant regression coefficient gave a significant effect. Meanwhile, communication (X3) does not have a significant effect. The dominant variable in this study is motivation (X2) which has an influence on the performance of the Flight Inspector at the Makassar Region V Airport Authority, after testing with the F-test and t-test which shows a very significant effect.